2020
DOI: 10.3368/npj.21.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Development of a vegetative propagation protocol forAsclepias tuberosa

Abstract: This article describes the first published report of a commercially viable vegetative propagation protocol for butterfly milkweed (Asclepias tuberosa L. [Apocynaceae]). Milkweed (Asclepias L.) species are regarded as a superior North American native pollinator taxa. Restoration of species into disturbed sites and increasing its use in managed landscape environments are a means of sustaining and promoting many threatened and endangered pollinators that rely on Asclepias spp. for nectar in the adult stage and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…IBA was also previously reported to be able to initiate root formation in stem cuttings of plants belonging to the Apocynaceae family, such as Carissa grandiflora ( Al-Mizory 2006 ), Holarrhena pubescens ( Baul et al . 2010 ), Carissa carandas ( Tanuja & Rana 2018 ) and Asclepias tuberosa ( Lewis et al . 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…IBA was also previously reported to be able to initiate root formation in stem cuttings of plants belonging to the Apocynaceae family, such as Carissa grandiflora ( Al-Mizory 2006 ), Holarrhena pubescens ( Baul et al . 2010 ), Carissa carandas ( Tanuja & Rana 2018 ) and Asclepias tuberosa ( Lewis et al . 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those offers suggested that planting of favored non-native hosts could have the unintended consequence of facilitating the spread of non-native, non-Apis bees in urban areas. As improved propagation methods facilitate breeding and production (Lewis et al, 2020) and our understanding of the influence of cultivars vs. species increases (Poythress and Affolter, 2018), more native plant species and cultivars will become available in the ornamental plant trade that have been bred specifically to attract and support pollinators. Currently there are a great many ornamental plant cultivars available on the market, yet there is little empirical information available to guide consumer choice regarding attractiveness to pollinators (Garbuzov and Ratnieks, 2014;Rollings and Goulson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The native distribution of the species extends from Ontario to Newfoundland in Canada, south to Florida, and west to Colorado. It is perhaps best known for the vital role it plays as a forage source for larval monarch (Danaus plexippus L.) butterflies (Hutchings 1923;Lewis et al 2020). Additionally, A. tuberosa is highly drought-tolerant and possesses a prolonged flowering and seed production season (Lewis et al 2020).…”
mentioning
confidence: 99%
“…It is perhaps best known for the vital role it plays as a forage source for larval monarch (Danaus plexippus L.) butterflies (Hutchings 1923;Lewis et al 2020). Additionally, A. tuberosa is highly drought-tolerant and possesses a prolonged flowering and seed production season (Lewis et al 2020). These attributes make it highly desirable for use in restoration and landscaping.…”
mentioning
confidence: 99%
See 1 more Smart Citation